Illicit financial flows in Mozambique’s natural resource sector: The effect of macroeconomic factors (Research, Society and Development, 2022)
The study investigates the illicit financial flows from the natural resource sector in Mozambique with a particular focus on the effect of macroeconomic factors. Relying on quarterly time series data (2008Q1-2019Q4), the study adopted the ARDL estimation procedure and a granger causality test for the purpose of analysis. From the results, it was revealed that real exchange rate and government budget deficit have a significant and positive effect on illicit financial flows from the natural resource sector in the long run. However, the short-run inflation as well as the government budget deficit and external debt were found to influence the movement of illicit financial flows from the natural resource sector in Mozambique. Furthermore, granger causality results revealed a bidirectional effect moving between illicit financial outflows and external debt, and between control of corruption and illicit financial outflows.